Draft Outline Fourth Five Year Plan Punjab State - Planning Commission (Planning Commission, 1965)
The Fourth Plan proposals, as Incorporated In this publication, were drafted before the present Emergency and will therefore need to be revised In the light of the new situation. On the one hand the defence requirements which must receive first priority have to be assessed In detail by the Government of India and on the other there Is uncertainty In regard to the nature and quantum of external assistance that will be available. The Planning Commission Is engaged on a study of the subject but the examination will take some time to complete.
Government of Punjab Planning Department Chandigarh